A study of the factors impacting on workforce distribution of Australian osteopaths: The perspectives of osteopathic students, academics and clinicians. (June 2020) - Steel, Amie; Dingle, Tess; Wardle, Jon; Adams, Jon
Abstract: Objective: The study aimed to investigate the major factors influencing osteopaths' choice of clinical workplace and their experience practising in their geographical location. Methods: Semi-structured interviews and focus groups with Australian osteopathic clinicians, academics and students. Results: Factors influencing practice location include personal factors and other external factors (such as financial and business skills, the practice environment, and the features of the destination). Osteopaths practising outside the greater Melbourne area describe their major challenges as the (1) lack of consistency of associates, (2) location of osteopathy programs, (3) characteristics of new graduates, and (4) expectations and availability of mentoring. Conclusions: The unique workforce distribution issues of the Australian osteopathic profession identifies new perspectives beyond the urban/rural divide commonly explored within health workforce literature to now include drivers, facilitators and barriers to relocation between urban centres. Implications for Practice: There is an uneven geographical distribution of osteopaths in Australia. Personal relationships impact on an osteopath's choice of practice location. Establishing practice in a new location is linked with personal history and self-perception. Osteopaths practising outside of areas with a large osteopathic community experience challenges.